Synthesis and structure of nitrile-solvated rare earth metallocene cations [Cp2Ln(NCR)3][BPh4] (Cp = C5Me5, C5H4SiMe3; R = Me, tBu, Ph). (8th January 2016) - Corbey, Jordan F.; Woen, David H.; Ziller, Joseph W.; Evans, William J.
Graphical abstract: In the presence of excess amounts of MeCN, t BuCN, and PhCN, the cationic rare earth tetraphenylborate complexes [(C5 Me5 )2 Ln][( μ -Ph)2 BPh2 ] form complexes containing just three nitriles [(C5 Me5 )2 Ln(NCR)3 ][BPh4 ], which have bent metallocene geometries with 137–140° (C5 Me5 ring centroid)–metal–(C5 Me5 ring centroid) angles. Abstract: The coordination chemistry of MeCN, t BuCN, and PhCN with the cationic rare earth metallocene complexes [(C5 Me5 )2 Ln][( μ -Ph)2 BPh2 ], 1 -Ln (Ln = Y, La, Gd), has been examined to determine how nitrile coordination will affect the metallocene geometry. Crystallographic determination of geometry was possible for [(C5 Me5 )2 Ln(NCMe)3 ][BPh4 ] (2 -Y, 2 -Gd ), [(C5 Me5 )2 Y(NC t Bu)3 ][BPh4 ] (3 -Y ), and [(C5 Me5 )2 Ln(NCPh)3 ][BPh4 ] (4 -La, 4 -Gd ). In each case, only three nitriles are found to coordinate and the metallocenes are bent with (C5 Me5 ring centroid)–metal–(C5 Me5 ring centroid) angles of 137–140°. The THF adduct, [(C5 Me5 )2 La(NCMe)2 (THF)][BPh4 ], 5 -La, was also crystallographically characterized. A similar result was observed with the yttrium metallocene of the trimethylsilyl-containing ligand (C5 H4 SiMe3 ) 1− : coordination of only three nitriles is found in [(C5 H4 SiMe3 )2 Y(NCMe)3 ][BPh4 ], 6 -Y, which has a 136.8° (C5 Me5 ring centroid)–Y–(C5 Me5 ring centroid) angle.